SYPHILIS IN PREGNANCY - Bjekic, Milan (HEALTH CARE, 2021)
Early syphilis has been increasing in the Republic of Serbia since 2010 and its infectivity for sexual partners lasts for a year from the moment of infection. The exception is pregnant women who, if left untreated, can transmit the infection to the fetus within four years of infection. Syphilis in pregnancy can cause miscarriage, stillbirth, low birth weight or congenital syphilis. The aim of this paper is to present the clinical manifestations, laboratory diagnostics and therapy of syphilis in pregnancy, as well as to sensitize medical workers to this disease and the introduction of mandatory serological screening tests for syphilis in all pregnant women.